(3fgGjI GdEOQGc aj OQGjI GdCadGcs - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s ((3eMeO Hf eMeO Hf eMeO GdSeQbfOi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg aGWQ GdSehGJ ahb GdCQVjf YHQg ddfGXQjf GdeJhSejf s
(3BNQgG (B:s
(3hEPG habfi Gddg JYGdi dGJeGe eG bUOJg hGfLGR eG hYOJg adfNJe GdcJGH MGeOjf Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B34 - (3U(B162 :s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B108 s
Keywords: (3Gdadcs